Respon Pertumbuhan Protocorm Anggrek Dendrobium nindii x Dendrobium Jaya Srani Terhadap Pemberian Berbagai Konsentrasi Ekstrak Jagung (Zea mays) Secara In Vitro - Putri Pasela Hernawati; Darso Sugiono; Nurcahyo Widyodaru Saputro (Peneliti.net, 2022)
The research was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, University of Winaya Mukti Sumedang from September to November 2020. This study aimed to obtain the best response to the administration of various concentrations of corn extract (Zea mays). on the orchid plant Dendrobium sp.The research method used is an experimental method with a single factor Completely Randomized Design (CRD) with 6 treatments and 5 replications. There were 6 treatment combinations, namely A (MS medium + 0% or without the addition of corn extract), B (MS medium + 8% corn extract), C (MS media + 9% corn extract), D (MS medium + 10% corn extract). ), E (medium MS + 11% corn extract), and F (medium MS + 12% corn extract). If the data were analyzed with variance and the F test at the 5% level showed significant results, then further tests were carried out with the Duncan Multiple Range Test (DMRT) at the 5% level to determine the best treatment.The results obtained in this study showed that there was a growth response on the parameters of the number of shoots, shoot height, number of leaves, time of root emergence, number of roots and root length on the protocorm Dendrobium sp by giving various concentrations of corn extract (Zea mays). The best treatment was found at a concentration of 9% corn extract giving optimal results with an average number of shoots 46.62, number of leaves 96.22 strands, and the fastest root growing time was 26 DAP.